Internacionalização de firmas de saneamento básico: análise de abordagens de negócios internacionais - Souza, Neusa Santos de (2012)
This work deals with the internationalization of firms belonging to the basic sanitation industry, a typically monopolist activity in which the State, held responsible for the services, may delegate the rights to exploration through public service concessions or other forms of public-private partnership. The general objective of the research is to compare the characteristics of the internationalization of sanitation firms with those foreseen by the selected International Business approaches and models. The research problem is related to the adequacy of established International Business theories to the explanation of idiosyncrasies of the path of internationalization of the firms in the water and sewerage industry. There were selected the Uppsala and the Transaction Costs Theory, the theoretical references having used elements of institutional theory and Industrial Economics, taking the specific market failures of this industry into account. This is a qualitative research, based in documental analysis. Firms selected were: : Veolia, Suez, Agbar, FCC, United Utilities, ACEA, RWE, Saur, Cascal and Biwater, which correspond to the ten largest in the world and they are responsible for roughly one fifth of the world water supply. Propositions verified are related to the pattern of internationalization, which in the sanitation industry is defined more upon specific windows of opportunity and not following the Uppsala pattern; and that the need for knowledge of local markets in host countries makes relevant the conjunction between political-institutional competences with specific technical competences. Propositions were confirmed and, against that background, the analysis suggests inadequacy of some assumptions of dominant theoretical models and the need of further theoretical elaboration so as to provide support to the internationalization process of this kind of firm